Combination of Controlling Nutritional Status Score and Systemic Immune-Inflammation Index as Predictors of Repeated Hospitalization in Chronic Kidney Failure Patients Undergoing Routine Hemodialysis - Lia Sasmithae; Ni Nyoman Sri Yuliani; Herlina Eka Shinta; Didin Retno Indah Palupi (International Journal of Health and Pharmaceutical (IJHP), 2026)
Repeated hospitalization is a major clinical problem among patients with chronic kidney disease (CKD) undergoing routine hemodialysis. Malnutrition and chronic systemic inflammation play important roles in the pathogenesis of complications in this population. This study aimed to analyze the association between the Controlling Nutritional Status (CONUT) score and the Systemic Immune-Inflammation Index (SII) with repeated hospitalization among patients with CKD undergoing routine hemodialysis. This analytical observational study employed a cross-sectional approach involving 121 patients with stage 5 CKD undergoing routine hemodialysis at dr. Doris Sylvanus Regional General Hospital, Palangka Raya, from January 2024 to July 2025. The CONUT score was calculated based on serum albumin, lymphocyte count, and total cholesterol levels. The SII was calculated using the formula (platelet count × neutrophil count)/lymphocyte count. Data were analyzed using Spearman's correlation test and multivariate logistic regression. The results showed a significant association between the CONUT score and repeated hospitalization (R = 0.462; p = 0.000), as well as between the SII and repeated hospitalization (R = 0.389; p = 0.000). Multivariate analysis showed that the CONUT score (OR = 1.619; 95% CI: 1.287–2.036; p = 0.000) and SII (OR = 1.097; 95% CI: 1.041–1.156; p = 0.001) were independent predictors. The model demonstrated good predictive performance with an AUC of 0.842 and a Hosmer–Lemeshow test result of p = 0.624. These findings indicate that the CONUT score and SII are significant independent predictors of repeated hospitalization among patients with CKD undergoing routine hemodialysis. The combination of these two indices has the potential to serve as a practical risk-screening tool in clinical practice.